SHOULDER PAIN - A. E. Barulin; O. V. Kurushina; V. V. Dumtsev (Медицинский совет, 2018)
Various joint pain syndromes are one of the frequent causes of treatment of patients not only to a traumatologist, but also to a neurologist. The urgency of the problem of pain syndromes in the shoulder is discussed in the article. Detailed anatomical and physiological features of the shoulder joint and periarticular soft tissues are highlighted. The characteristic of the most common etiological and pathogenetic mechanisms of the development of pain syndrome in the region of the shoulder joint is given. Part of the article is devoted to the clinical features and diagnosis of pain in the shoulder region, depending on the etiological factor of pain. In the article discussed modern pharmacological and non-pharmacological methods of treatment of shoulder pain. A clinical example of differential diagnosis of pain and treatment with drug Nimesil is considered.